LESER TRELAT SIGN IN THE DIAGNOSIS OF OCCULT NEOPLASMS-CASE REPORT - Jahic, Vildana (Medical Research, 2022)
Leser Ttrelat (LT) sign (syndrome) is a rare, characteristic clinical phenomenon that is manifested by a sudden, eruptive, appearance of multiple itchy seborrheic keratoses (SK) that sometimes coincide with occult malignancy. A 73-year-old patient came for examination of numerous, large seborrheic keratoses (SK) on the skin. According to the patient,s statement, SK did not occur suddenly and “eruptively“. Nevertheless, ultrasound and endoscopic evaluation were advised to the patient to exclude the Leser Trelat phenomenon. The patient was then diagnosed with an occult, asymptomatic rectal neoplasm. Occurrence of numerous seborrheic keratoses (especially if they are "eruptive", large and bizarre in shape), should raise suspicion of LT phenomenon, or internal malignancy in the patient, and result in relevant diagnostic procedures to detect possible latent malignancy. It would be wise for the doctors of all disciplines to be acquainted with the existence of the LT sign (syndrome) and the possible clinical implications of the same.